Response modalities and the cognitive architecture underlying action control: Intra-modal trumps cross-modal action coordination - Weller, Lisa; Pieczykolan, Aleks; Huestegge, Lynn (Cognition, 2022)
Performing two actions at the same time usually hampers performance. Previous studies have demonstrated a strong impact of the particular effector systems on performance in multiple action control situations. However, an open question is whether performance is generally better or worse in situations in which two actions within the same effector system are coordinated (intra-modal actions: e.g., two pedal or two manual actions) compared to situations requiring two different effector systems (cross-modal actions: e.g., a manual combined with a vocal action). Performance differences can be predicated, among others, in the light of encapsulation accounts. Encapsulation of modules on the output side of processing would suggest that actions in two different modules can be triggered simultaneously without significant interference between the actions. Thus, cross-modal actions should lead to better performance compared to intra-modal actions. We investigated this issue in two basic experiments, in which participants responded to a single stimulus (thereby maximizing control over input and central processing stages) with one or two either intra-modal or cross-modal responses (manual-manual vs. manual-oculomotor/manual-vocal in Experiment 1/2, respectively). The results represent clear evidence for a performance advantage of intra-modal over cross-modal action control across both effector system combinations and independent of the particular spatial compatibility relation between responses. The results suggest performance benefits by taking advantage of integrated, holistic representations of intra-modal action compounds.